COHESION IN FOREIGN LANGUAGE WRITING - Nyak Mutia Ismail; Lisma Linda (Universitas Islam Negeri Alauddin Makassar, 2018)
It is important to keep the cohesion and coherence when writing; this is where the use of cohesive devices starts to be taken into account. This study sought the types of cohesive devices used by undergraduate students in their writing. The qualitative discourse analysis was used as the design of this research. The data were collected from seven undergraduate students as the respondents who were in the 6th semester at a private university in Aceh. These respondents were asked to write a descriptive text approximately 200 words in length and they were given forty-five minutes to finish their writing. The result unveiled that the type of cohesion devices which was majorly used was addition, as there are 94% of the additive device usage. Then, 75% refers to the use of cohesive devices as comparison, 56% as consequential, and 40% as temporal device. In can be concluded that the students use more addition in writing. As a suggestion, it is essential to shed light on their ability to employ cohesive devices more on other types in balance as it is necessary in contrasting, comparing, sequencing, giving exception, and illustrating.